STRATEGY FOR INCREASING EMPLOYEE ENGAGEMENT OF MILENIALS AT PT TELKOM INDONESIA REGIONAL 1 MEDAN USING THE ADDIE METHOD - Stefanus Yudha; Vivi Gusrini Rahmadani Pohan; Meilita Tryana Sembiring (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
This research is motivated by the number of employees at PT Telkom Indonesia Regional 1 Medan of 53.92% who are Generation Y. According to several previous studies, the engagement of Y-generation is the lowest when compared to previous generations. As a form of prevention, in this study an analysis was carried out regarding what dimensions/factors were not well perceived within PT Telkom Indonesia, Tbk Regional 1 Medan. The purpose of this research is to provide advice to the management of PT Telkom Indonesia Regional 1 Medan in the form of a strategy to increase engagement among employees of PT Telkom Indonesia, Tbk Regional 1 Medan. The type of research used in this research is descriptive quantitative research. The population in this study were employees of PT Telkom Indonesia, Tbk Regional 1 Medan with samples taken in this study were 67 respondents. The data collection method used was a questionnaire using a Gallup Q-12 with a Likert scale of 1-5, an open questionnaire and interviews. The results of this study using the ADDIE method found that the growth dimension is a dimension that according to respondents should be increased again in PT Telekomunikasi Indonesia, Tbk Regional 1 Medan.